2009
DOI: 10.1002/ceat.200900192
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations and Dynamic Simulation of Diesel Particulate Filter Systems

Abstract: The complex dynamic behavior of a diesel particulate filter (DPF) system during the regeneration process can be well predicted by detailed numerical simulation. Simulation studies for diesel oxidation catalyst (DOC) and catalyzed DPF (CDPF) based on detailed kinetic experiments are presented for the relevant gaseous species and soot. Heterogeneous 1D models are used and solved with the PDEX-Pack simulation package. The influence of soot morphology on the reaction kinetics in terms of reactive surface is experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In various cases a DPF is connected by a wide-angled cone to the engine exhaust pipe. Examples are the recently developed catalytic DPFs that simultaneously remove the PM and oxidize the effluent organic compounds, and the new DPFs that reduce both the PM and NOx emissions. A potentially dangerous temperature excursion occurs following a rapid deceleration of the diesel engine or a sudden shift to idle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In various cases a DPF is connected by a wide-angled cone to the engine exhaust pipe. Examples are the recently developed catalytic DPFs that simultaneously remove the PM and oxidize the effluent organic compounds, and the new DPFs that reduce both the PM and NOx emissions. A potentially dangerous temperature excursion occurs following a rapid deceleration of the diesel engine or a sudden shift to idle.…”
Section: Discussionmentioning
confidence: 99%
“…Circumventing these occasional local temperature excursions is still a major technological challenge in the design, operation, and control of a DPF. Numerous experimental and theoretical studies have attempted to understand and predict the undesirable formation of the high temperature excursions in a DPF. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diesel particulate filter (DPF) is an effective tool to control soot from diesel engine. Generally, the exhaust temperature ranges from 150 • C to 450 • C, while the oxidation temperature of soot exceeds 550 • C. It is, therefore, necessary to raise the temperature for soot combustion, but excessive soot combustion temperature will damage the filter material [5]. Therefore, a superior solution is to reduce the oxidation reaction temperature of soot using catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a catalytic DPF has been developed, which simultaneously removes the PM and oxidizes the emitted uncombusted organic compounds. In these cases the exhaust pipe is connected to the larger diameter DPF by a wide-angled cone (diffuser). The experiments of Stratakis and Stamatelos , revealed that the cone caused mal-distribution of the inlet velocity to the various channels.…”
Section: Introductionmentioning
confidence: 99%